George Gissing On-Screen: An interview with Morgan Watkins on The Limehouse Golem - Ue, Tom (Film International, 2017)
Abstract
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maWluLjE1LjQuMTM4Xzc